An investigation into factors influencing intention to pay zakat: evidences from Nigeria - Muhammad, Sani Adamu (2016)
The research of intention to pay zakat in Kano Nigeria is still at the early stage. The main objective of this study is to examine factors influencing intention to pay zakat in Kano Nigeria. Questionnaires were collected from businessmen and businesswomen operating in Kano Nigeria using a cross-sectional study design. Questionnaires were distributed and collected through the personally-administered method. A total of 524 businessmen and businesswomen in Kano participated in this study. Partial Least Squares Structural Equation Modelling (PLS-SEM) was used and tested the study hypotheses. The study reveals that attitude toward zakat evasion, attitude toward moral reasoning, peer influence, zakat knowledge, quality of zakat distribution and perception of board capital are important determinants of intention to pay zakat in Kano Nigeria. However, attitude toward ethnic diversity, influence of religious leaders, zakat system structure and enforcement of zakat law are insignificant. Overall, the results indicates that, the study model provides a good understanding of the factors that influence intention to pay zakat specifically in Kano Nigeria. Finally, the study discussed theoretical, methodological contribution, practical implications as well as limitations and suggestions for future studies.